Enhancing self-regulation and approaches to learning in first-year college students: a narrative-based programme assessed in the Iberian Peninsula - Rosário, Pedro (2010)
A programme to enhance first-year college students’ self-regulated learning strategies is proposed and assessed in two samples, one from the University of Oviedo (Spain) and the other from the University of Minho (Portugal). Each sample was divided into two groups (experimental and control). The Spanish sample comprised 44 students in the experimental group and 40 in the control group, whereas in the Portuguese sample, the number of students was 48 and 44, respectively. The narrativebased intervention programme is organised around a set of fictional letters from a first-year college student in which he reports his own academic experiences. Each letter focuses on a learning strategy as an opportunity to teach and enhance the students’ deep approaches to learning and their self-regulated learning processes. In both samples, findings confirm the programme efficacy to teach efficient learning strategies and to promote self-regulation. Implications for college students and for teaching are discussed.